Final report and appendices (OLADE QuitoEC, 1991)
Includes the OLADE Caracas Declaration which establishes the lines of action regarding intra-regional energy cooperation and supply security; the institutional role of the state in the energy sector; and recommendations to member countries to adapt a common stance for the United Nations Conference on Environment and Development.
DC